The Bajo Segura Fault Zone: Active blind thrusting in the Eastern Betic Cordillera (SE Spain) - Alfaro, P.; Bartolomé, R; Borque, M.J.; Estévez, A.; García-Mayordomo, J.; García-Tortosa, F.J.; Gil, A.J.; Gràcia, E.; Lo Iacono, C.; Perea, H. (Journal of Iberian Geology, 2012)
The Bajo Segura Fault Zone, located at the NE end of the Eastern Betic Shear Zone, has been the site of some of the most intense seismic activity on the Iberian Peninsula in the historical and instrumental time periods. This structure is an active blind fault that does not show any surface rupture. It is characterised by a set of ENE-WSW trending blind thrust faults that offset the Triassic basement and cause active folding of the Upper Miocene-Quaternary sedimentary cover. The main active structures of this fault zone are two ENE-WSW striking reverse blind faults, the Torremendo and the Bajo Segura Faults, and several secondary NW-SE striking dextral faults (San Miguel de Salinas, Torrevieja and Guardamar Faults). These structures continue offshore to the east. From geological, geomorphological and geodetic data, we obtain fault slip rates between 0.2 and 0.4 mm/yr, whereas other authors have proposed higher values ranging between 0.75 and 1 mm/yr. The fault zone can generate earthquakes with maximum estimated magnitudes (Mw) from 6.6 to 7.1 and has approximate recurrence intervals between 4.500 and 21.500 years.